2011
DOI: 10.1109/tpel.2011.2106222
|View full text |Cite
|
Sign up to set email alerts
|

UPQC-S: A Novel Concept of Simultaneous Voltage Sag/Swell and Load Reactive Power Compensations Utilizing Series Inverter of UPQC

Abstract: This paper introduces a new concept of optimal utilization of a unified power quality conditioner (UPQC). The series inverter of UPQC is controlled to perform simultaneous 1) voltage sag/swell compensation and 2) load reactive power sharing with the shunt inverter. The active power control approach is used to compensate voltage sag/swell and is integrated with theory of power angle control (PAC) of UPQC to coordinate the load reactive power between the two inverters. Since the series inverter simultaneously de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(131 citation statements)
references
References 23 publications
0
131
0
Order By: Relevance
“…In the UPQC-DG, with storage, such as battery and flywheel storage, the shunt part of UPQC is in connection with the PCC, whereas the series part is positioned prior to the PCC in series with the grid. In case the storage is present, the DC link may be hooked up with it [2] …”
Section: Upqc-dgmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UPQC-DG, with storage, such as battery and flywheel storage, the shunt part of UPQC is in connection with the PCC, whereas the series part is positioned prior to the PCC in series with the grid. In case the storage is present, the DC link may be hooked up with it [2] …”
Section: Upqc-dgmentioning
confidence: 99%
“…Lee et al [1] proposed a control strategy for UPQC-Q which offers minimum active power injection by which voltage sag can be compensated effectively and economically. Khadkikar et al [2] suggested the control method of series inverter of UPQC by using power angle control(PAC) series inverter can compensate both voltage sag/swell and load reactive power sharing between two inverters. As the model controls both active and reactive power flow the model named as UPQC-S. Khadem et al [3] proposes a new topology of UPQC i.e.…”
mentioning
confidence: 99%
“…Several researches mainly focus on capacity optimization of the UPQC [13][14][15][16]. However, the proposed strategy focuses on the limitation of current-carrying capability due to the following reasons.…”
Section: Analysis Of Current-carrying Requirementsmentioning
confidence: 99%
“…Compared with [14], the demand of active power injection using UPQC-S strategy P inj ' can be given by…”
Section: Comparative Analysis Of Active Power Injectionmentioning
confidence: 99%
See 1 more Smart Citation